2016
DOI: 10.1542/peds.2015-4573
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned From Newborn Screening for Critical Congenital Heart Defects

Abstract: Newborn screening for critical congenital heart defects (CCHD) was added to the US Recommended Uniform Screening Panel in 2011. Within 4 years, 46 states and the District of Columbia had adopted it into their newborn screening program, leading to CCHD screening being nearly universal in the United States. This rapid adoption occurred while there were still questions about the effectiveness of the recommended screening protocol and barriers to follow-up for infants with a positive screen. In response, the Cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 40 publications
0
57
0
13
Order By: Relevance
“…Differences in state CCHD screening laws include whether the mandate would be funded, whether all of the infants would be screened or whether exceptions to screening were permissible (special care nurseries, premature infants, out of hospital births, screening at altitude) and whether any aggregate or individual CCHD screening data would be reported. Most states choose to implement the algorithm recommended by the AAP with New Jersey, Tennessee, and Minnesota being among the few exceptions [6]. Data collection, the extent to which education was provided, and the monitoring of implementation by state public health departments also vary greatly.…”
Section: State-by-state Advocacymentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in state CCHD screening laws include whether the mandate would be funded, whether all of the infants would be screened or whether exceptions to screening were permissible (special care nurseries, premature infants, out of hospital births, screening at altitude) and whether any aggregate or individual CCHD screening data would be reported. Most states choose to implement the algorithm recommended by the AAP with New Jersey, Tennessee, and Minnesota being among the few exceptions [6]. Data collection, the extent to which education was provided, and the monitoring of implementation by state public health departments also vary greatly.…”
Section: State-by-state Advocacymentioning
confidence: 99%
“…This list of core conditions was expanded in 2016, this time by an expert panel convened by the Centers for Disease Control (CDC) and the American Academy of Pediatrics (AAP) to include coarctation of the aorta, double-outlet right ventricle, Ebstein's anomaly, interrupted aortic arch, single ventricle, and other critical cyanotic lesions not specified. The expert panel also acknowledged the added benefit of identifying secondary targets, including hemoglobinopathy, hypothermia, infection (including sepsis), lung disease, noncritical CHD, persistent pulmonary hypertension, and other hypoxemic conditions as important public health targets of CCHD screening in the U.S. [6].…”
Section: Introductionmentioning
confidence: 99%
“…The staff, required to perform the test, need to be thoroughly trained in the screening procedures, interpretation of results and knowing how to respond to babies with failed screens. (18) KZN and other resource limited provinces encounter numerous barriers to implementing routine oxygen saturation screening. These barriers include poorly funded health services in the public sector caring for an enormous patient load.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Globally, pouring support on its implementation as a screening tool in early identification of CCCD make an unignorable potential candidature in the panel. [18][19][20][21][22][23] It has been reported to be a safe, useful tool to screen neonates for cardiac malformation particularly in rural areas with limited infrastructure. Aksande AM et al reported that hypoxemia in neonates (SPO2 <90%) after 4 hours of birth calls for further assessment including echocardiography.…”
Section: Discussionmentioning
confidence: 99%